Bilateral bifid mandibular canal - Mahnaz Sheikhi; Hamid Badrian; Sajad Ghorbanizadeh (Wolters Kluwer Medknow Publications, 2012)
One of the normal interesting variations that we may encounter in the mandible is bifid mandibular canal. This condition can lead to difficulties when performing mandibular anesthesia or during extraction of lower third molar, placement of implants, and surgery in the mandible. Therefore diagnosis of this variation is sometimes very important and necessary.